Perioperative cell salvage blood transfusions in endonasal angiofibroma surgery at Groote Schuur Hospital - Wasl, Hisham (Division of Otorhinolaryngology, 2015)
Surgical approaches for many tumours are often limited by blood loss, exposure and risk to vital anatomical structures; therefore, the standard of care for certain skull base tumours has become endoscopic transnasal resection. Other surgical disciplines often use cell salvage techniques, but review of the otolaryngology literature reveals very few case reports. General surgery procedures are often carried out in a contaminated field and concerns have been raised about its safety. This study investigates the value and safety of salvage-type autologous blood transfusion during the endoscopic resection of juvenile nasopharyngeal angiofibromas (JNA). Methods: Because JNA is a rare vascular nasal tumour, the study extended over a 3-year period to obtain adequate patient numbers. All patients undergoing endoscopic resection during this period were included in the population sample. Ten patients with JNA were identified and underwent embolization prior to endoscopic resection. In all cases the intraoperative blood salvage apparatus was used. Close post-operative monitoring was performed.